Lost Classrooms, Found Streets: Understanding the Roots and Realities of Deviant Behaviours Among Out-of-School Children in Africa - Abdallah Jacob Seni (Universitas Nurul Jadid, 2025)
This article presents a systematic review of the deviant behaviours of out-of-school street children in Africa. It aims to explore the underlying factors that drive children to the streets, the forms of deviant behaviours they engage in, and the public perception of this phenomenon. The review examined 15 empirical studies selected from academic databases, including Google Scholar, Scopus, Web of Science, Dimensions, and PubMed, in accordance with the PRISMA guidelines. Data were analysed thematically using a narrative synthesis approach. The findings reveal that poverty, parental violence, and family disintegration are the main factors pushing children into street life, resulting in the denial of access to basic education. Street children were found to engage in deviant behaviours such as begging, violence, substance abuse, theft, and prostitution. While most of the public holds negative perceptions of these children, some view their struggle as a sign of resilience and survival. The review highlights the urgent need for integrated interventions involving government, social organisations, and educational stakeholders to break the cycle of poverty and provide educational opportunities for street children. Promoting inclusive basic education is essential for empowering these vulnerable children and shaping a more equitable future.